Effectiveness of Paul Model Critical Thinking Training on Nurses' Knowledge and Skills: A Quasi-Experimental Study in a Type C Hospital - Murna Elliza; Zifriyanthi Minanda Putri; Yuanita Ananda (LPPM Universitas Harapan Bangsa, 2024)
Low knowledge and competence in implementation are thought to be the cause of the low quality of nursing care. Paul's model of critical thinking training is carried out to improve the quality of nursing care. The aim of the research is to analyze the influence of Paul's model of critical thinking training on the knowledge and competence of nurses in implementing nursing care. The research used a quasi-experimental approach with a pre-test and post-test nonequivalent control group design, the sample size was 33 intervention groups and 33 control groups with a purposive sampling technique. Bivariate analysis used the Wilcoxon and Mann Whitney tests because the data distribution was not normal. The research results showed that the average knowledge in the intervention group increased by 32% and the average skills increased by 48%, while in the control group the average knowledge and skills only increased by 24%. There was a significant difference between the intervention group after training and the control group given the module (p < 0,05). There is an influence of Paul's model of critical thinking training and modules on knowledge and skills (p < 0,05). Paul's model of critical thinking training can increase nurses' knowledge and skills in implementing nursing care